Neglected Texts, Trajectories, and Communities: Reshaping World Literature and East Asia. Issue 3 (2nd July 2016) - Thornber, Karen L.
ABSTRACT: This article first calls attention to the contrast between, on the one hand, East Asia's global prominence and the region's long intertwined literary history, and on the other hand, the failure of the field of world literature to integrate fully East Asian literatures. I then probe two case studies of world literature from East Asia: the thirteenth-century Mongolian Secret History of the Mongols (Mong. Mongγol-un niγuča tobčiyan, Chn. Yuanchao mishi, M元朝秘史, c. 1228); and the twentieth-century Korean writer Yi Ch'ŏngjun's (이청준) novel Your Paradise (Tangsindǔl ǔi ch'ŏn'guk, 당신들의 천국, 1976) on the Sorokdo leprosarium. These two narratives have circulated extensively within East Asia as well as globally, yet neither has been included in discourse on world literature nor, in the case of Yi Ch'ǒngjun's novel, in discourse on medical humanities.